Basicity of Some Pyridinophanes in Gas Phase and Acetonitrile – a DFT Study. Issue 27 (17th July 2018) - Despotović, Ines
Abstract: The gas phase proton affinities and basicities of a [1.1.1]‐(2, 6)‐pyridinophane and its derivatives having one ‐CH2 ‐ bridge replaced by ‐CH=CH‐ and ‐CH2 ‐CH2 ‐ are examined by the DFT B3LYP/6‐311+G(2df, p)//B3LYP/6‐31G(d) method. The calculated proton affinities are within the range of 253.8 and 294.8 kcal mol −1 . The upper‐scale basicity is consequence of unfavorable steric interactions in neutral bases and diminishing of former in conjugate acids with forming of intramolecular hydrogen bonds (IMHB) being amplified by substitution in the para position of pyridine rings by electron‐releasing substituents. The inspection of the nature of IMHBs reveals that IMHB is of a bifurcated type with energy spanning a range between 5.7 and 7.4 kcal mol −1 . The basicities of pyridinophanes are examined in acetonitrile. It is found that their p K a values span a range between 18.9 and 31.3 units. Abstract : The gas phase proton affinities and basicities as well as the basicities in MeCN of [1.1.1]‐(2, 6)‐pyridinophane and its derivatives are examined using DFT calculations. The calculated proton affinities span a range between 253.8 and 294.8 kcal mol −1, while p K a values lie between 18.9 and 31.3 units.